Workshop Pembuatan Soal Literasi Membaca Berbasis Asesmen Kompetensi Minimum bagi Guru MGMP Bahasa Indonesia Kabupaten Rokan Hilir - Muhammad Mukhlis; Latif Latif; Melda Amriyani Putri; Hani Khoirunnisa (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The background to the implementation of this service is that the assessment of reading literacy competence is one of the assessments carried out by schools and the government in mapping the overall quality of students in the aspect of reading literacy. Therefore, students need to get reading literacy questions as their provision and experience to face the assessment. Teachers as the frontline in training and teaching students must also have the competence to make reading literacy questions based on AKM. Initial information was obtained by the teacher's obstacles in making reading literacy questions based on AKM. These constraints are 1. Setting an interesting stimulus and according to the student's level. 2. Create a question model that is in accordance with the AKM level. 3. Make a form of complex multiple choice questions. 4. determine the assessment criteria of each form of questions. 5. Determine the question indicators. These constraints become a reference and basis for giving workshops to participants. The results of PKM activities can be concluded that activities can provide experience to participants in making AKM-based reading literacy questions. Participants or teachers are very happy to get the training. As a result, it is expected that teachers can expand and create reading literacy questions that require critical thinking skills. Furthermore, it is hoped that all participants can inspire other teachers in their respective schools.